(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Rational use of drugs forms the corner stone of successful implementation of rational use of medicines. Irrational drug prescription leads to ineffective treatment, occurrence of adverse effects, prolonged duration of illness, suffering of patients, and an increased economic burden to society. Objective: To see the pattern and rationality of drugs prescribed in OPD paediatrics patients in a tertiary care hospital in Dhaka city. Methodology: A cross-sectional study was conducted at Department of Paediatrics, Dhaka National Medical College Hospital including pediatric age group prescriptions below 12 yrs for the duration of November 2018 to February 2019. Referral prescriptions and prescriptions of seriously ill patients were excluded from study. Results: Various drug formulations were prescribed in the study. Most commonly found formulation was syrups and suspensions 304(60.8%) followed by solutions 69 (13.8 %) .On an average, number of drugs prescribed per prescription was 3.12. Most commonly diagnosed disease was pneumonia in 105 (21%) of patients. 262 (52.4 %) prescriptions included one or more antimicrobial agents. Most commonly used antimicrobial agents were Amoxycillin in 62 (59%) patients followed by Ciprofloxacin in 27 (77.5%). The average cost per prescription was 216 tk. Conclusion: The present study may provide feedback on concept of rationality in use of drugs to improve prescribing pattern. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 24-29